study of antipruritic effect of citrus bigaradia(sour orange) - f SHarififar; F Moatar; A.A Mohaghegh zadeh (Journal of Kerman University of Medical Sciences, 1996)
pruritis is a common dermatic condition which can be the symptom of many localized and systemic infections,for which these is no specific treatment.most of the drugs used only lessen the symptoms,and they all have side effects.based on this,and since in Iranian traditional medicine sour orange fruit has been implicated as having antipruritic effects,in this study the latter effect was studied.at first the plant was gathered, identified,scientifically named and eatracted by percolation wath ethanol 80%.the cream of the plant and its relevant placebo was formulated using vanishing cream base.on the basis of the spilker,s novel double blind method,antipruritic activity of sour orange cream,calamin cream and placebo on 27 volunteers were evaluated during 110  minutes.in this expriment the bulb of scilla was examined using ratio 4mg in 5ml water as pruritogen agent.the results were evaluated with pair t-test.the findings indicated that calamin and sour orange creams had the false level of 10% and 20% in proportion to placebo,therefore we can conclude that despite on indication of a relative improvement,we can not conclude a definite effect based on the sample size in this study.